Pengaruh Fasilitas Rumah Sakit Dan Harga Pelayanan Terhadap Word Of Mouth Melalui Kepuasan Pasien - Rina Ari Ruliati; Eko Budi Satoto; Abadi Sanosra (STIE Mandala Jember, 2023)
The purpose of this study was to obtain an in-depth picture and provide empirical evidence regarding the effect of hospital facilities and prices on patient satisfaction through word of mouth. The research location is Fatimah Islamic Hospital Banyuwangi. The number of respondents studied were 100 people. Data collection techniques using a questionnaire. The results showed that hospital facilities had a positive and significant effect on word of mouth at the Fatimah Islamic Hospital in Banyuwangi. The price of service has a positive and significant effect on word of mouth at the Fatimah Islamic Hospital in Banyuwangi. Hospital facilities have a positive and significant effect on patient satisfaction at the Fatimah Islamic Hospital in Banyuwangi. The price of service has a positive and significant effect on patient satisfaction at the Fatimah Islamic Hospital in Banyuwangi. Patient satisfaction has a positive and significant effect on word of mouth at the Fatimah Islamic Hospital in Banyuwangi. Hospital facilities have a positive and significant effect on word of mouth with patient satisfaction as an intervening variable at the Fatimah Islamic Hospital in Banyuwangi. The price of service has a positive and significant effect on word of mouth with patient satisfaction as an intervening variable at the Fatimah Islamic Hospital in Banyuwangi.